River teeth : twenty years of creative nonfiction - Mackall, Joe; Lehman, Daniel W. (Daniel Wayne), 1950-; Atwan, Robert (University of New Mexico Press, 2020)
"Cofounded by Joe Mackall and Daniel Lehman in 1999, River Teeth: A Journal of Nonfiction Narrative has become a nationally recognized leader in publishing a range of creative nonfiction, including essays, memoir, and literary journalism. To celebrate twenty years of publishing great nonfiction, the founding editors have brought together a selection of their favorite all-time essays published in River Teeth by up-and-coming authors as well as luminaries such as Lee Martin, Chris Offutt, Angela Morales, Brenda Miller, Judith Kitchen, and Andrew Dubus III. With a foreword and an essay also by Robert Atwan, River Teeth: Twenty Years of Creative Nonfiction serves as a great example of the diversity of nonfiction writing on offer in the twentieth-first century"-- Provided by publisher.
Keywords: American prose literature -- 21st century.; Prose literature -- 21st century.; Reportage literature, American.; Prose américaine -- 21e siècle.; Prose -- 21e siècle.; Littérature de reportage américaine.; American prose literature; Prose literature; Reportage literature, American; 2000-2099